Comparative effects of acupuncture and metformin on insulin sensitivity in overweight/obese and lean women with polycystic ovary syndrome and insulin resistance: a post hoc analysis of a randomized trial - Cao, Jie; Nie, GuanHua; Dai, Zhihao; Shan, Dan; Wei, Zhihong (Frontiers in Medicine, 2023)
The study explored the efficacy of acupuncture and metformin in enhancing insulin sensitivity among women with polycystic ovary syndrome (PCOS) and insulin resistance (IR), distinguishing between overweight/obese and lean groups.Methods: A post-hoc analysis of a randomized trial (NCT02491333) was undertaken.Participants were women aged 18-40 with PCOS and IR. They were randomized to receive true acupuncture with a placebo, metformin with sham acupuncture, or sham acupuncture with a placebo for four months, with follow-up visits over three months.Our study, involving 339 women, assessed the differential impact of acupuncture and metformin on insulin sensitivity in overweight/obese (BMI ≥ 24) versus lean women (BMI < 24). Primary outcomes measured changes in the Homeostatic Model Assessment of Insulin Resistance (HOMA-IR) at 4 and 7 months. Secondary outcomes assessed changes in glucose area under the curve (glucoseAUC) during the oral glucose tolerance test (OGTT) and BMI changes at 4 months.Results: Overweight/obese participants were generally older with higher measurements in various health metrics, but lower levels in specific hormonal metrics compared to lean women (p < 0.05). Among overweight/obese women, metformin outperformed acupuncture in reducing HOMA-IR levels (p=0.004) and showed a significant drop from the baseline after 4 months (p < 0.05). In contrast, acupuncture's effect on HOMA-IR didn't significantly differ from sham acupuncture at 4 and 7 months. For lean women, metformin and acupuncture showed comparable improvements in HOMA-IR, with notable declines at 4 and 7 months (p < 0.05). Acupuncture proved more beneficial for lean women than their overweight/obese counterparts after 4 months (p=0.021).In overweight/obese women with PCOS and IR, acupuncture was less effective than metformin in enhancing insulin sensitivity. However, in lean women, acupuncture's efficacy was comparable to metformin. Further studies are required to validate these observations.